Working toward a theoretical model for source comprehension in everyday discourse. Issue 5 (3rd July 2021) - Braasch, Jason L. G.; Kessler, Erica D.
ABSTRACT: Comprehension substantially benefits from attending to, thinking about, and mentally representing the sources of any presented information. Such processes require mental effort and unfortunately people do not always engage in such activities. The current article presents a nascent, evolving model of discourse comprehension that formalizes mechanisms to predict and explain people's strategic use of source information. The discrepancy-induced source comprehension (D-ISC) model and its theoretical assumptions describe the moment-by-moment cognitive processes in which readers engage when they interact with potentially contradictory or controversial messages presented by different information sources. The utility of the model is supported by evidence from a growing research base examining single- and multiple-text comprehension experiences. The D-ISC model is also useful for suggesting future directions that could help build more-nuanced understandings of the ways that diverse readers engage in sourcing activities within everyday discourse contexts.